I RUSSIAN CONGRESS WITH FOREIGN PARTICIPANTS “EMERGENCY ENDOSCOPY”. MATERIALS OF CONFERENCE. PART 3 - T. P. Pinchuk (Неотложная медицинская помощь)
I Russian congress with foreign participants “Emergency endoscopy”. Materials of conference. Part 3.